Dialogic Organization Development: The Theory and Practice of Transfor mational Change - Bushe, Gervase R. (EDS Publications Ltd., 2015)
Dialogic Organization Development is a compelling alternative to the c lassical action research approach to planned change. Organizations are seen as fluid,socially constructed realities that are continuously cr eated through conversations and images change happens when those conve rsations and images change. Leaders and consultants can help foster, s upport, or accelerate the emergence of transformational possibilities by encouraging disruptions to taken-for-granted ways of thinking and a cting and the use of generative images to stimulate new organizational conversations and narratives. Dialogic OD is a different mindset, but it s also the previously unrecognized underpinning of such diverse ch ange methods as Appreciative Inquiry, the Art of Convening, Future Sea rch, and many more.